Bioresorbable pins and screws in paediatric traumatology - Benz, Gert; Kallieris, Dimitrios; Seeböck, T.; McIntosh, A.; Daum, Roland (European journal of pediatric surgery, 1994)
Thieme E-Books & E-Journals
Elektronische Reproduktion der Druck-Ausgabe 25. März 2008
Gesehen am 15.04.2024